Extractivism and the civilizing crisis - Ticona Fernández Dávila, Rubén (2020)
The 21st century began with very complex problems that have been producing a great ecological, social and economic impact: natural catastrophes, social inequalities, wars and migrations of scale. All this in a context of globalization with exclusion and segregation of an increasingly precarious and vulnerable population. This situation produced by the establishment of an extractive and predatory model that has been installed in the Latin American region, which constantly threatens the possibility of sustainability as a way of life. The main objective of this article is to reflect on the fundamentals of the current crisis and its link with the region's development model and the risks to sustainability. For this, and hermeneutical analysis is proposed, the theoretical approach of decolonial sociology is used, which allows us to situate ourselves in our Latin American.